دور الإتصال الداخلي في تعزيز الانتماء التنظيمي عبر المؤسسة الاقتصادية الخدماتية - بن شعايب, قادة اسامة (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
تهدف هذه الدراسة إلى التعرف على تأثير الاتصال الداخلي على الانتماء التنظيمي في المؤسسات الاقتصادية الخدماتية، وكذلك إلى تحديد العوامل التي تسهم في تحسين فعالية الاتصال الداخلي وذلك من أجل تعزيز أداء الموظفين وزيادة رضاهم الوظيفي. استخدمت الدراسة المنهج الوصفي التحليلي، وأدوات جمع البيانات شملت المقابلات والملاحظة بالمشاركة ، وتم تطبيقها على عينة مكونة من 22 موظف في قطاع الخدمات اتصالات الجزائر خلال الفترة من 12 ماي إلى 20 ماي 2024 ، بالإعتماد على المتغيرات المفسرة مثل أساليب الاتصال الداخلي، وبيئة العمل، والقيادة، والمتغير التابع وهو مستوى الانتماء التنظيمي . توصلت هذه الدراسة إلى أن هناك علاقة إيجابية قوية بين فعالية الاتصال الداخلي والانتماء التنظيمي للموظفين. كما أظهرت النتائج أن بيئة العمل الداعمة وأساليب القيادة الفعّالة تساهمان بشكل كبير في تعزيز فعالية الاتصال الداخلي . وتوصلت نتائج الدراسة كذلك إلى أن تحسين مهارات التواصل لدى الإدارة والموظفين يساهم في رفع مستوى الانتماء التنظيمي بشكل ملحوظ. اقترحت الدراسة على المؤسسات الاقتصادية الخدماتية تطبيق برامج تدريبية متخصصة في تطوير مهارات الاتصال الداخلي وتعزيز البيئة التنظيمية الداعمة لزيادة الانتماء التنظيمي لدى الموظفين .ا
اتصالات الجزائر فرع مستغانم نموذجا
This study aims to identify the impact of internal communication on organizational commitment in service-oriented economic institutions, as well as to determine the factors that contribute to improving the effectiveness of internal communication in order to enhance employee performance and increase job satisfaction. The study employed a descriptive analytical method, and data collection tools included interviews and participant observation. It was conducted on a sample of 22 employees in the Algerian telecommunications service sector from May 12 to May 20, 2024, relying on explanatory variables such as internal communication methods, work environment, leadership, and the dependent variable, which is the level of organizational commitment. The study found that there is a strong positive relationship between the effectiveness of internal communication and employees' organizational commitment. The results also showed that a supportive work environment and effective leadership methods significantly contribute to enhancing the effectiveness of internal communication. Furthermore, the study's results indicated that improving communication skills among management and employees notably raises the level of organizational commitment. The study suggested that service-oriented economic institutions implement specialized training programs to develop internal communication skills and foster a supportive organizational environment to increase employees' organizational commitment.
Keywords: internal communication, organizational commitment, service-oriented economic institutions, employee satisfaction.; الاتصال الداخلي، الانتماء التنظيمي، المؤسسات الاقتصادية الخدماتية، رضا الموظفين.